Autonomous Architecture for UAV-based Agricultural Survey - Mondal, Sabyasachi; Williamson, Alex A.; Xu, Zhengjia; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2020)
This paper presents the concept of autonomous architecture for UAVs to minimize human involvement for agricultural surveying. Agricultural surveying applications include monitoring crop health and collecting ground truth data for treatment and harvest planning. The proposed architecture can automate the entire surveying process and helps farmers to obtain specific and essential knowledge about the crop more quickly. This architecture helps to increase crop yields while reducing operating costs. The autonomy is achieved by integrating functional modules such as Mission Planning, image processing, task allocation, and communication. This work is focused on describing the mission planning and task allocation since image processing is not within the scope.